Subcutaneous immunization with the fusion protein ΔA146Ply-SP0148 confers protection against Streptococcus pneumoniae infection. (January 2022) - Wang, Yao; Xia, Lingyin; Wang, Guangli; Lu, Huifang; Wang, Hui; Luo, Shilu; Zhang, Tao; Gao, Song; Huang, Jian; Min, Xun
Abstract: Pneumococcal SP0148 and pneumolysin (Ply) derivatives are important vaccine candidates. SP0148 is a conserved lipoprotein with high immunogenicity produced by Streptococcus pneumoniae . We have previously demonstrated that SP0148 can confer protection against fatal infections caused by S. pneumoniae . ΔA146Ply is a noncytotoxic mutant of Ply that retains the TLR4 agonistic effect and has mucosal and subcutaneous adjuvant activities suggested to induce protective immunity against S. pneumoniae infection. In this study, we constructed the fusion protein ΔA146Ply-SP0148, composed of ΔA146Ply and SP0148, and evaluated the immunoprotective effect of the fusion protein. When mice were subcutaneously immunized with the fusion protein ΔA146Ply-SP0148, high levels of anti-ΔA146Ply and anti-SP0148 IgG antibodies were induced in the serum. Specific antibodies can bind to a variety of different serotypes of S. pneumoniae . Compared with mice immunized with ΔA146Ply and SP0148 alone, mice immunized subcutaneously with the fusion protein ΔA146Ply-SP0148 with Al(OH)3 had a higher survival rate when challenged by a lethal dose of S. pneumoniae, and they also had significantly lower lung bacterial loads and milder lung inflammation. In addition, mice immunized subcutaneously with the fusion protein ΔA146Ply-SP0148 stimulated strong Th1, Th2, and Th17 cell responses. In summary, these results suggest that subcutaneous immunization with the ΔA146Ply-SP0148 fusion protein can protect mice against fatal pneumococcal infection and lung infection. The fusion protein ΔA146ply-SP0148 can be a new pneumococcal vaccine target. Highlights: Subcutaneous immunization with the ΔA146Ply-SP0148 with Al(OH)3 could protect mice against S. pneumoniae lethal infection. ΔA146Ply-SP0148 can elicit both cellular immunity and humoral immunity. Subcutaneous immunization with ΔA146Ply-SP0148 without adjuvant significantly increased the survival rate of mice.